LANGUAGE, KNOWLEDGE, AND HIGHER EDUCATION IN GLOBALIZATION10 (2020)
This book offers a vision rather than a definition of knowledge. A vi-sion that occurs with exaltation and experiences throughout the reading of this book, very similar to how the mind works, in a very unexpected way. Language, communication, language, speech, geo-politics, economics, science, technology —everything is the source, cause, and effect of knowledge. However, a proposal appears be-tween the lines for a transitory definition.It is likely to believe at certain point of our intellectual life that we have already understood what knowledge is, but it should not be like that, for there will always be something else that completes the compre-hension process, which is transitory and continuous. This dynamic process has brought us to 2020 with enormous challenges every day. The way we explain certain perverse metaphors used in everyday conversation, in formal exhibitions, in television programs, which do not really reveal knowledge but rather hide it, make us think in a self-critical way about our use of the word. The author calls these metaphors flippant and the examples are simple but compelling. Here is why we are not able to solve simple problems such as gar-bage or plastic, despite the existence of knowledge. There is too much positivism.The concept of humanities as the cornerstone of educational quality, which begins from the perspective of artist Doris Salcedo, is clearly appreciated in chapter five, where the key concepts of the Critical Educational Model with a Competency Approach are exposed. It is not without some controversies that it could well be debated in pub-lic, such as the unification of an educational model or its criticism of the consequences of the prosperous and pondered entertainment in-dustry in critical thinking.